A study of wireless communication links on a body centric network during running - Sabti, H. A.; Thiel, D. V. (Procedia Engineering, 2014)
Wireless Body Area Networks (WBAN) is a developing area of research that allows wireless sensors to be attached in or on the human body. The object of this paper is to establish a WBAN to acquire movement and physiological data using sensors at various places on the body and to send their data to a central node. This node processes and re-transmits information to a remote computer (locally or in the cloud) for further processing and presentation. The real time feedback that can be provided by these nodes is very important in sport for the athletes, coaches and the viewing public. However, the challenge is to sustain good wireless communications between the nodes while the athletes are moving. In this paper we report an investigation into the best node locations on the human body to achieve maximum connectivity to a receiving unit (gateway) located on the chest, as well as the best angular window for the nodes to transmit the data during typical human movements such as running and walking. The results showed that while the distance between the transmitting and receiving nodes changes significantly, the presence of scattering from limbs provides the most significant effect on the received signal strength. These measurements demonstrated that a received signal strength of greater than -70 dBm is available for 20% to 74% of the time for different node locations. The use of an accelerometer sensor at each node allows these positions to be identified in real time for burst transmission to occur reliably.